Simultaneous determination of Pb and Cd in low-cost jewelry using differential pulse voltammetry. Issue 45 (2nd November 2016) - Ferreira, Taimara Polidoro; de Sousa, Rafael Arromba; Lowinsohn, Denise
Abstract : The simultaneous electrochemical determination of lead (Pb) and cadmium (Cd) in low-cost jewelry was achieved using differential pulse voltammetry (DPV). Abstract : The simultaneous electrochemical determination of lead (Pb) and cadmium (Cd) in low-cost jewelry was achieved using differential pulse voltammetry (DPV). The presented voltammetric detection via standard addition shows possible simultaneous analyses of Cd and Pb. The detection limit of 1.13 × 10 −4 % m m −1 for lead and 1 × 10 −3 % m m −1 for cadmium were obtained. The recovery rate ranged between 99 and 110% for Cd and 99–105% for Pb. Nine different low-cost jewelry pieces were analysed. Some were purchased from local trade while others were confiscated goods from the police force.